Julie Coleman: A History of Cant and Slang Dictionaries. Volume I: 1567-1785 / Julie Coleman: A History of Cant and Slang Dictionaries. Volume II:1785-1858 - McDermott, Anne (Lexikos, 2007)
These two beautifully printed and presented volumes document a complete history of dictionaries of English cant and slang from 1567 to 1858. Coleman investigates the wealth of dictionaries and glossaries of cant and slang that are, as she puts it, 'far more often used than studied' but which, nonetheless, form an essential part of the 'tangled tradition' (I: 1) of early lexicographical study. She goes beyond just documenting this history, though, and the range of her work is wider than that implied by the title. She investigates the social history behind these dictionaries, the criminal (auto)biographies that gave rise to some of them, how these dictionaries in their turn were used in some literary texts from Beggar's Opera to Guy Mannering and how they contributed to a culture that became obsessively interested in crime. In the process Coleman turns what could have been dull chronology into a lively and intellectually-engaging account.